Characterization of the marketing strategies adopted by Comigo Agropecuaria Store - Iporá Unit - GO (Research, Society and Development, 2020)
The current dynamic that permeates the market - competitive and globalized - requires organizations to focus on the relationship with customers, transcending the offer of products and / or services, but rather recognizing what the customer wants. In this sense, new business models were incorporated, with emphasis on the agro-industrial cooperative system, especially aligned with the Brazilian agricultural vocation. Thus, this research aims to survey the marketing strategies adopted by the COMIGO Cooperative - Iporá Unit - Goiás, considering it to be the largest supplier of agricultural inputs in the municipality. The methodological procedures used were, bibliographic review of topics related to marketing, composed of marketing and agroindustrial cooperative, as well as the realization of a semi-structured interview with the manager of the unit object of this study. The results show that the actions taken are defined at the administrative headquarters by the communication department and cover all business units. At the same time, actions that meet the interests of the local community are perceived, such as sponsorship, support for social actions, partnerships with educational institutions and associations.